Implementation Of Islamic Boarding School Management Strategy In The Era Of Industrial Revolution 4.0 - Rini Susilowati; Acep Nurullah; Amrullah Amrullah; Ahmad Patih (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This research aims to describe the implementation of the management strategy of the training at Baitul Hidayah Islamic Boarding School Bandung in the era of Industry Revolution 4.0. The method used in this research is a qualitative descriptive analysis approach. The selection of informants in this study was done using purposive sampling techniques (sampel bertujuan). Data collection techniques are done by means of observation, interviews, and documentation studies. The phase of data analysis involves data condensation, data presentation, and conclusion. The results of this study show that Pesantren Baitul Hidayah Islamic Boarding School Bandung implemented strategy management through four stages, namely: First, environmental analysis is carried out in two ways: external and internal. External factors are the demand for human resources with increased capabilities in the field of technology, while internal factors are strong leadership commitment. Second, the formulation of the strategy is made by the trainer, Baitul Hidayah Islamic Boarding School Bandung, by formulating the vision, mission, and objectives as well as the strategy of curriculum development. Third, the implementation of the strategy is done to implement the plan that has been made in strategy formulation. At this stage of implementation, there is a learning process that is integrated with technology, i.e., a YouTube-based online review that is carried out every morning; and fourth, an evaluation of the training strategy of Baitul Hidayah Islamic Boarding School Bandung is performed to see if the implementation is in line with the planned strategy formulation. Evaluation is carried out in a number of ways, including in the form of a sudden inspection and other evaluations using a group evaluation system.